Implementation of Constitutional Court Decision No. 57/PUU-IX/2011 Regarding Smoking-Prohibited Areas and Smoking Areas: A Siyasah Qadhaiyyah Perspective - Siregar, Irmansyah Husin (LEGAL BRIEF, 2025)
This study examines the implementation of Constitutional Court Decision No. 57/PUU-IX/2011, a landmark ruling that reinforces the right to a healthy environment by mandating the establishment of smoke-free areas and the provision of designated smoking rooms in public facilities. Focusing on its application at the Grand Mosque of Medan, the research adopts the perspective of siy?sah qadh?’iyyah within Islamic legal thought to assess the extent to which the decision achieves its intended goals. The findings reveal several implementation challenges, including inadequate infrastructure, weak supervision, and limited public awareness regarding the legal obligations related to smoking regulations. Through the lens of siy?sah qadh?’iyyah, the study offers both legal and ethical insights into the decision’s effectiveness, particularly in upholding substantive justice and enhancing public welfare. Moreover, the decision aligns with the objectives of maq??id al-shar?‘ah, particularly in the protection of life (?if? al-nafs), intellect (?if? al-‘aql), and the environment (?if? al-bi’ah). The research concludes that integrating contemporary legal mandates with Islamic values is crucial to building a legal framework that is not only just and enforceable but also sustainable and socially resonant.